Inhibitors of recombinant protein-tyrosine phosphatase 1B (PTP1B) from Khaya senegalensis: Towards a strategic target for therapeutic intervention in trypanosomiasis - Fatima Amin Adamude; Ikenna Nnamdi Ezeaku; Abraham Ehinomhen Ubhenin; Ifeanyi Peter Onyeka; Ahmad Adamu Ambi; Ikechukwu Robert Uroko; Emeka John Dingwoke (Elsevier, 2022)
Background: Tyrosine dephosphorylation, catalyzed by protein-tyrosine phosphatase (PTP), prevents trypanosome differentiation to a procyclic form that lacks diverse mechanisms for survival within the mammalian host's bloodstream. Thus, differentiation to a procyclic form in the mammalian host's bloodstream would be potentially lethal to the parasite. This demonstrates that PTP is a critical regulator of trypanosome differentiation, making it a strategic therapeutic target for trypanosomiasis.Purpose: The in vitro inhibitory effect of seven compounds from the active fraction of Khaya senegalensis stem bark (4‑hydroxy-2-butanone, 1,3-butanediol, 2-methylpropyl butanoate, n-tridecanoic acid (CH3-(CH2)11-COOH), n-tetratriacontane, n-hexadecanoic (CH3-(CH2)14-COOH), and 14-pentadecenoic acid (CH2=CH-(CH2)12-COOH)) on the enzymatic activity of recombinant human PTP1B (MBL-SE332-0050) was investigated in this study.Method: The inhibition study was performed according to the standard procedure for analytical experiment and was monitored spectrophotometrically. PTP1B was assayed with 10 mM of p-nitrophenylphosphate. Bioassay-guided fractionation of methanol stem bark extract from K. senegalensis yielded the potent PTP1B inhibitors. Sodium orthovanadate was used as the positive control for inhibition. The kinetic parameters were determined by Lineweaver-Burk plots and calculated using Sigma Plot (SPCC Inc., Chicago, IL, USA)Results: The active fraction that contains the seven compounds inhibited PTP1B dose-dependently with an IC50 of 1.32 µM. Lineweaver-Burk plots revealed that PTP1B was inhibited non-competitively with a Ki of 0.46 ± 0.03 mg/ml, while sodium orthovanadate inhibited the enzyme competitively with an IC50 of 1.02 µM and Ki of 0.26 ± 0.01 mg/ml. Cleavage of the substrate para-Nitrophenylphosphate (pNPP) by PTP1B showed a KM of 4.99 mM and Vmax of 0.053 µmol/min.Conclusion: The mixture of compounds tested is potent PTP1B inhibitors that could serve as scaffolds for new trypanocidal drug candidates that target protein-tyrosine phosphatase activity.